2018
DOI: 10.1111/ejn.13896
|View full text |Cite
|
Sign up to set email alerts
|

Influence of auditory attention on sentence recognition captured by the neural phase

Abstract: The aim of this study was to investigate whether attentional influences on speech recognition are reflected in the neural phase entrained by an external modulator. Sentences were presented in 7 Hz sinusoidally modulated noise while the neural response to that modulation frequency was monitored by electroencephalogram (EEG) recordings in 21 participants. We implemented a selective attention paradigm including three different attention conditions while keeping physical stimulus parameters constant. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Poor spatial segregation in EEG is typically seen for auditory evoked cortical responses such as N1 and P2 components (Pereira et al, 2014) . It is also the case of tracking at theta frequencies where EEG scalp distribution of coherence maximum at the vertex and at 33/48 bilateral temporo-occipital electrodes is compatible with N1 topography, as also evident in previous studies (Müller et al, 2018;Ng et al, 2013) .…”
Section: Effect Of Added Auditory Noise On Speech Brain Trackingsupporting
confidence: 83%
See 1 more Smart Citation
“…Poor spatial segregation in EEG is typically seen for auditory evoked cortical responses such as N1 and P2 components (Pereira et al, 2014) . It is also the case of tracking at theta frequencies where EEG scalp distribution of coherence maximum at the vertex and at 33/48 bilateral temporo-occipital electrodes is compatible with N1 topography, as also evident in previous studies (Müller et al, 2018;Ng et al, 2013) .…”
Section: Effect Of Added Auditory Noise On Speech Brain Trackingsupporting
confidence: 83%
“…Still, the neural mechanisms allowing the human brain to decode speech signals in real time are poorly understood . Based on electroencephalographic (EEG) or magnetoencephalographic (MEG) recordings, it was shown that listerner's auditory cortices track the time course of speaker's speech temporal envelope at 0.5 Hz (delta frequencies) and 4-8 Hz (theta frequencies) (Ahissar et al, 2001;Bourguignon et al, 2013;Broderick et al, 2017;Di Liberto et al, 2015;Ding et al, 2017;Ding and Simon, 2014;Gross et al, 2013;Horton et al, 2013;Keitel et al, 2018;Kösem and van Wassenhove, 2016;Luo and Poeppel, 2007;Meyer and Gumbert, 2018;Molinaro et al, 2016;Müller et al, 2018;O'Sullivan et al, 2014;Peelle et al, 2013;Pellegrino et al, 2011;Puschmann et al, 2017; . As delta and theta frequencies match with phrasal/sentence and syllable repetition rates respectively, it has been hypothesized that corresponding brain oscillations subserve the chunking of incoming speech into relevant segments for further speech recognition (Ahissar et al, 2001) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neural oscillations shape speech perception (e.g., Bosker and Ghitza, 2018). Many studies demonstrated that selective attention modulates neural entrainment and leads to a selectively enhanced representation of the attended stream (e.g., O’Sullivan et al, 2014; Mirkovic et al, 2015, 2016; Petersen et al, 2017; Müller et al, 2018). For instance, Petersen et al (2017) presented continuous speech either in quiet or masked by a competing talker at different signal-to-noise ratios (SNRs) to participants with hearing impairment and investigated the influence of hearing loss, SNR, and attention on neural tracking of speech.…”
Section: Introductionmentioning
confidence: 99%